Association of mental health, quality of life, and SARS-CoV-2 infection in individuals in need of care: Results from a multicentre registry study - Karoline Lukaschek; Heidi Hentschel; Marietta Rottenkolber; Martin Alberer; Susanne Winter; Maria Sebastia͂o; Florian Arend; Tobias Dreischulte; Ildikó Gágyor; Anita Hausen; Michael Hoelscher; Christian Janke; et al. (PLoS ONE, 2025)
Objective Investigating the association between mental health, quality of life, and SARS-CoV-2 infection in individuals in need of care compared to independent living individuals. Individuals in need of care include both care home residents and those receiving care either through an outpatient care service or from family members. Methods This cross-sectional study assessed symptoms of depression (PHQ-9 > 9) and anxiety (GAD-7 > 9), quality of life (EQ-5D-5L, EQ-VAS), dementia (SIS), SARS-CoV-2 infection and socio-demographic variables in the total sample (N = 978, 64.4% female, mean age: 77.5 ± 13.8 years) and subgroups (study group, STG, n = 532, individuals in need of care, SARS-CoV-2 positive; control group 1, CG1, n = 213, individuals in need of care, SARS-CoV-2 negative; control group 2, CG2, n = 233, independent living individuals, SARS-CoV-2 positive). Multivariate logistic regressions were performed. Results Depressive symptoms (PHQ-9 > 9) were significantly associated with lower quality of life in the total sample (EQ-VAS: OR 0.96, 95% CI 0.95–0.97, p < 0.001; EQ-5D-5L: OR 0.14, 95% CI 0.07–0.29, p < 0.001) and across all subgroups. Anxiety (GAD-7 > 9) was significantly associated with lower quality of life in the total sample (EQ-VAS: OR 0.97, 95% CI 0.95–0.98, p < 0.001; EQ-5D-5L: OR 0.19, 95% CI 0.08–0.50, p < 0.001) and all subgroups except CG1. In individuals in need of care with COVID-19, depressive symptoms were additionally associated with symptomatic infection (OR 3.47, 95% CI 1.45–8.28, p = 0.005). Conclusion Depression and anxiety were significantly associated with reduced quality of life, irrespective of living environment or SARS-CoV-2 infection status, underscoring the need for targeted mental health interventions in older adults. While our model explained a considerable portion of the variability in depression and anxiety, further research is needed to account for the remaining proportion.